A simple proof of the Polar Decomposition Theorem - Wójcik, Paweł (Annales Mathematicae Silesianae, 2016)
In this expository paper, we present a new and easier proof of the Polar Decomposition Theorem. Unlike in classical proofs, we do not use the square root of a positive matrix. The presented proof is accessible to a broad audience.